Potret Gerakan Ahmadiyah di Indonesia dalam Buku Prof. Iskandar Zulkarnain - Titian Ayu Nawtika; Muhammad Yuslih (JURNAL PENELITIAN KEISLAMAN, 2021)
Ahmmadiyah is a religious organization founded by a reformer named Mirza Ghulam Ahmad from India. This paper aims to portray the doctrine and movement of Ahmadiyah in Indonesia in Prof.'s book. Iskandar Zulkarnain. As for the research by Prof. Iskandar Zulkarnain uses a historical approach. From the research results, there are several teachings of Muhammadiyah which include: (1) al-Mahdi and al-Masih; (2) (mujaddid); (3) The death of Prophet Isa as; (4) revelation; (5) prophetic; (6) caliphate; (7) jihad. The entry of Ahmadiyah started with the Ahmadiyya Movement in Indonesia at the beginning of the studies in 1920 by Maulana Kwadja Kamluddin, a prominent Lahore Ahmadiyya in India and then landed in Surabaya. In its journey, Ahmadiyah's position among Indonesian people is difficult because of three factors, namely: (1) controversy in the theological field; (2) internal organizational chaos; (3) one of the Ahmadiyah figures named Muhammad Sabitun entered the PKI carriage.